2005
DOI: 10.3201/eid1101.040257
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Background ofEscherichia coliand Extended-spectrum β-Lactamase Type

Abstract: ESBL-producing E. coli may arise from interactions between ESBL type, strain genetic background, and selective pressures in various ecologic niches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
95
5
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(115 citation statements)
references
References 39 publications
10
95
5
5
Order By: Relevance
“…Therefore, the 42.9% bla(SHV) detection rate in this study suggested that many dogs with diarrhoea in Iran may harbor extended-spectrum β-lactam (ESBL)-resistant E. coli. This finding is a cause for concern because extended-spectrum β-lactams are critical for treatment of bacterial infections in humans and animals (Bradford 2001) and E. coli isolates habouring bla(SHV) have been reported to exhibit multidrug resistance (Branger et al 2005, Bush and Jacoby 2010, Geser et al 2011. Thus, the presence of bla(SHV) gene in the examined isolates in this study, pose serious threat to public health as well as that of the examined dogs since compromise in antibacterial therapy may result following zoonotic transmission of the organisms (Warren et al 2001).…”
Section: 4% a A D ( A 1 ) T E T ( A ) T E T ( B ) D F R ( A 1 ) S mentioning
confidence: 99%
“…Therefore, the 42.9% bla(SHV) detection rate in this study suggested that many dogs with diarrhoea in Iran may harbor extended-spectrum β-lactam (ESBL)-resistant E. coli. This finding is a cause for concern because extended-spectrum β-lactams are critical for treatment of bacterial infections in humans and animals (Bradford 2001) and E. coli isolates habouring bla(SHV) have been reported to exhibit multidrug resistance (Branger et al 2005, Bush and Jacoby 2010, Geser et al 2011. Thus, the presence of bla(SHV) gene in the examined isolates in this study, pose serious threat to public health as well as that of the examined dogs since compromise in antibacterial therapy may result following zoonotic transmission of the organisms (Warren et al 2001).…”
Section: 4% a A D ( A 1 ) T E T ( A ) T E T ( B ) D F R ( A 1 ) S mentioning
confidence: 99%
“…Phylogroups A (18%) and B1 (7%), which are associated with animal or human commensal strains, were less frequently represented. All isolates of phylogroups B2, A, and D corresponded to subgroups B2 3 , A 1 , and D 1 , respectively, which are the most common ones within each phylogenetic group (31). The 43 clinical isolates were classifi ed into 32 PFGE types (B2 3 , 13; D 1 , 10; A 1 , 6; and B1, 3).…”
Section: Epidemiologic Backgroundmentioning
confidence: 99%
“…This collection has 52.6% of strains resistant to amoxicillin, a well-known indicator of the frequency of antibiotic resistance in bacterial populations. Identical patterns of the relationship between antibiotic resistance and mutation frequencies were obtained with two other collections encompassing both commensal and extra-intestinal pathogenic strains: a collection of 117 highly resistant strains producing extended spectrum b-lactamases (100% of strains resistant to amoxicillin) (Branger et al 2005) and a collection of 119 strains isolated in the 1980s with a low level of antibiotic resistance (11.8% of strains resistant to amoxicillin) (data not shown).…”
mentioning
confidence: 99%